تقييم معلومات القابلات حول العناية التمريضية خلال الدور الثاني من المخاض - البيرق, كوكب (Latakia University Journal -Medical Sciences Series, 2017)
تعتبر رعاية الأمومة غير الكافية أثناء الحمل والولادة مسؤولة بشكل كبير عن الخسائر السنوية الكبيرة لكل من الأمهات الماخضات و مواليدهن. لذا هدفت هذه الدراسة إلى تقييم معلومات القابلات حول العناية التمريضية خلال الدور الثاني من المخاض, ودراسة العلاقة بين المعلومات الشخصية ومستوى معلومات القابلات خلال الدور الثاني للمخاض. أجريت هذه الدراسة الوصفية في ثلاث مستشفيات في مدينة اللاذقية على عينة من 160 قابلة. أظهرت النتائج أن مستوى معلومات القابلات تجاه المرحلة الثانية من المخاض كان متوسط, ولدى دراسة تأثير المعلومات الشخصية على مستوى معلومات القابلات حول المرحلة الثانية من المخاض تبين وجود علاقة ذات دلالة إحصائية بين العمر ومستوى معلومات القابلات وبين المستوى التعليمي و مستوى معلوماتهم, كما أظهرت الدراسة عدم وجود علاقة ذات دلالة إحصائية بين الخبرة ومستوى معلومات القابلات. أوصت هذه الدراسة بضرورة تصميم برنامج تعليمي للقابلات لرفع مستوى معلوماتهن لتقييم وتقويم وتحسين نوعية العناية المقدمة للماخض، والتأكيد على إقامة دورات تدريبية دورية بغرض تحديث معلوماتهن مع الإشراف المستمر على أدائهن.Considered inadequate maternity care during pregnancy and delivery largely responsible for the big annual losses for each of the parturient mothers and their newborns. So this study aimed to assess the midwives knowledge regarding the management of second stage of labor, and to find out the association between their knowledge and personal data during second stage of labor. This descriptive study was conducted in three hospitals at lattakia city, on a sample of 160 midwife. Results of the study showed that the level of midwives information to the second stage of labor was average, and the study of the impact of personal data on the level of midwives information about the second stage of labor show a statistically significant relationship between age and the level of Midwives Information, and between educational level and the level of their knowledge. The study also showed that There were no statistically significant differences between the experience and the level of information midwives relationship. The study recommends that; installing in-service educational program for Midwives to upgrade the techniques necessary to assess, evaluate and improve the quality of care rendered to laboring women, and to put an emphasis on conducting training course for the Midwives in order to change their malpractices and updating their knowledge with regular supervision on their performance.